Sistem Informasi Manajemen Pendidikan: Dari Dukungan Negara Hingga Sistem Dukungan Keputusan Pada Pendidikan Tinggi - Syahrul Syahrul (Institut Agama Islam Negeri (IAIN) Kendari, 2016)
Utilization of information and communication technology products in the management of education has become a new trend, because it is proven to improve the effectiveness and efficiency of the management of educational institutions. One of the greatest contributions is the Management Information System of Education/EMIS), which serve to provide comprehensive information needed for decision-making in educational institutions. This awareness is not only felt by the developed countries but also developing. Nigeria became one of the developing countries who awakened to the importance of information systems in the management of education. Beberapan challenges faced are: inadequate funding, inability to integrate data and data systems, inadequate skills development in the use of data at all levels, inability to capture expenditure and cost data in EMIS, the inability to develop Record-student based EMIS. The importance of information systems unit feels more on the level of education, as support in making strategic decisions.Keywords: Education Management Information System, Decision Making